Food Banking, Ethical Sensemaking, and Social Innovation in an Era of Growing Hunger in the United States. (April 2016) - Elmes, Michael B.; Mendoza-Abarca, Karla; Hersh, Robert
This article considers the critical role that food bank leaders play in sensemaking around the ethical and justice dimensions of hunger and food-related illnesses in the United States. It presents the discourses of industrial agriculture and food justice and, using an illustrative case study, proposes a preliminary model of ethical sensemaking. This model serves as a starting point for understanding how some (but not all) food bank leaders in the United States have been triggered to engage in ethical sensemaking and adopted a variety of innovative, sustainable, and just approaches to food banking that try to address the root causes of growing levels of hunger in the United States. The article concludes with an invitation to consider this investigation through the lens of Dewey's moral imagination and Gergen's forms of inquiry that generate practices to solve social problems and that invite researchers to participate in world-making.